THE USE OF CODE SWITCHING BY LECTURER IN ONLINE LEARNING AT GRADUATE PROGRAM OF UNIVERSITAS NEGERI MAKASSAR - Rahman, Kurnia; Mahmud, Murni; Amin, Fatimah Hidayahni (JTechLP: Journal of Technology in Language Pedagogy, 2024)
The aims of this research are to find out the types of code-switching, to know the function of code-switching used by the lecturer in online learning at graduate programs, and to know the perceptions of students towards the use of lecturer’s code-switching in online learning at graduate programs. In investigating the research’s topic, the researcher used a mixed method. The subject of this research was the lecturer and students of Universitas Negeri Makassar, at English Education Magister Program. The researcher used observation with an audio-video recorder and questionnaire as instruments in this research. The researcher has drawn three points as the conclusion. The researcher found that the lecturer used 3 types of code-switching, and intra-sentential switching is the dominant type that is used by the lecturer. There were 9 nine functions of code-switching that can be identified in this research, addressee specification, interjection, loanwords, message qualification, transfer of the subconscious markers, proper name, quotations, message reiteration, and personalization versus objectification. Then the researcher found three new functions, those are shows concern for the students, confirming, and reprimanding the students. The researcher also found that the students expressed a positive perspective towards the use of lecturer's code-switching in online classes with a percentage of 96,6%.